Establishment of an In Vitro regeneration protocol of Gerbera (Gerbera Jamesonii) from leaf, flower bud and flower stalk explants of two Gerbera varieties - Tahsin, Promi (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.